PENGARUH TINGKAT SUKU BUNGA DAN PDRB TERHADAP SIMPANAN MASYARAKAT PADA BANK-BANK UMUM DI PEKANBARU - Dirgansari Subagia Dirgansari Subagia; Sumarno Sumarno '; Riadi Armas Riadi Armas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effect of interest rate and GDP on public deposits in Commercial Banks in Pekanbaru. This research was conducted in Singapore and as a data source is Bank Indonesia in Pekanbaru and the Central Bureau of Statistics in Pekanbaru. The method used is a method of quantitative analysis . The data used in this study is time series data from the years 2000-2013, namely the data amount of public deposits, interest rates on deposits and total GDP of Pekanbaru. The data analysis technique used is multiple linear regression. The result showed that the level of interest rates and GDP simultaneously affect the public deposits. This is based on the results of analyzes, calculations show of F > F table (143,917 > 3,982). Partially, the interest rate does not affect the public deposits. This is evidenced by the t test, a variable interest rate obtained t < t table (-0,823 <1,796). However, the partial GDP effect on public deposits. This is evidenced by the t test, GDP variables obtained t > t table (9,431> 1,796). So it can be concluded that the interest rate and the GDP effect on public deposits with a contribution of 96,3% and the remaining 3,7% is influenced by other factors not examined such as the level of public confidence, the facilities provided by banks and others.Keywords : influence, interest rates, GDP, public deposits